Low Grade Appendiceal Mucinous Neoplasm: A Report of Three Cases - Sharma, Nisha; Karna, Alina; Jha, Abhimanyu (Journal of Institute of Medicine Nepal, 2020)
Low-grade appendiceal mucinous neoplasm (LAMN) is an uncommon malignancy with varied clinical features. The most alarming complication of this neoplasm is seeding of mucin into the adjacent peritoneum leading to pseudomyxoma peritonei (PMP). We report three cases of LAMN. Two cases were seen post appendicectomy in 23-year old and 36-year old females. The third case was seen in 53-year-old male post Whipple procedure and hemicolectomy. LAMNs are often diagnosed incidentally, as clinical presentation is barely specific and resembles acute appendicitis. Hence it is imperative to examine all appendicectomy specimens not to miss cases of appendiceal mucinous neoplasm which can have implications on the further management of the patient.